Optimasi ph dan Suhu Proses Sakarifikasi Fermentasi Simultan dalam Produksi Bioethanol dari Ubi jalar - Harsojuwono, Bambang Admadi; Arnata, I Wayan (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 1, No. 1, 2014)
The Research objective was to obtain the optimum pH and temperature of simultaneous fermentation scarification (SFS) process on the ethanol production of the sweet potato hydrolyzed. This research used the block random design with factorial experiment. First factor was pH (4.5 ; 5.0 ; 5.5) and the second factor was temperature (30, 35, 40 and 45 oC). The research was conducted with the following stages : production of sweet potato hydrolyzed by enzyme in the liquidation process, preparation of S. cerevisiae culture and simultaneous fermentation scarification process. The results showed that the optimum simultaneous fermentation scarification process on temperature of 35oC and pH 4,5 that produce the ethanol of 5,32% (v/v) with the ethanol produce efficiency of 35,79% ; fermentation efficiency of 70,16% and yield of 11,79%. Key words: sweet potato, simultaneous fermentation scarification, pH and temperature